Novel Scopoletin Derivatives Kill Cancer Cells by Inducing Mitochondrial Depolarization and Apoptosis - Shi, Zhixian; Chen, Li; Sun, Jianbo (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Natural products and their molecular frameworks have been explored as invaluable sources of inspiration for drug design by means of structural modification, computer-aided drug design, and so on. Scopoletin extracting from multiple herbs exhibits potential anti-cancer activity in vitro and in vivo without toxicity towards normal cells. Objective: The study aims to obtain new scopoletin derivatives with enhanced anti-cancer activity. We performed chemical structure modification and researched the mechanism of anti-tumor activity. Methods: In this study, we considered scopoletin as a lead compound, designed and synthesized a series of scopoletin derivatives via introducing different heterocyclic fragments, and their chemical structures were characterized by NMR spectra (1H NMR and 13C NMR) and HRMS(ESI). The antiproliferative activity of target compounds in four cancer cell lines (MDA-MB-231, MCF-7, HepG2, and A549) was determined by the MTT assay. Compound 11b was treated with Ac-cys under different reaction conditions to explore the thiol addition activity of it. The Annexin V/PI and JC-1 staining assay were performed to investigate the anti-tumor mechanism of 11b. Results: Novel compounds 8a-h and 11a-h derivatives of scopoletin were synthesized. Most of the target compounds exhibited enhanced antiproliferative activity against different cancer cells and reduced toxicity towards normal cells. In particular, 11b displayed the optimal antitumor ability against breast cancer MDA-MB- 231 cells with an IC50 value of 4.46 μM. Compound 11b also cannot react with Ac-cys under the experimental condition. When treated with 11b for 24 h, the total apoptotic cells increased from 10.8% to 79.3%. Besides, 11b induced the depolarization of mitochondrial membrane potential. Conclusion: Compound 11b was more active than other derivatives, indicating that the introduction of thiophene fragment was beneficial for the enhancement of antitumor effect, and it was also not an irreversible inhibitor based on the result that the α, β-unsaturated ketones of 11b cannot undergo Michael addition reactions with Accys. Furthermore, studies on the pharmacological mechanism showed that 11b induced mitochondrial depolarization and apoptosis, which indicated that 11b killed cancer cells via a mitochondrial apoptotic pathway. Therefore, in-depth research and structure optimization of this compound is warranted.
Keywords: apoptosis